Analisis Kelayakan Finansial Olahan Keletek Udang di Poklahsar Tanjung Jaya Bersama Kuala Jambi Tanjung Jabung Timur - Hariski, M; Ramdhani, Farhan; Hasanah, Hasanah; Wulandari, Wulandari; Roiska, Riris; Asyraf, Muhyi; Khoiriyah, Muhimatul (Universitas Galuh, 2026)
The fishery product processing industry has an important role in increasing the added value and welfare of coastal communities. Kuala Jambi District, East Tanjung Jabung Regency has abundant shrimp raw material potential, opening up opportunities for the development of processed products such as shrimp chips. There is a lack of studies that assess the financial feasibility aspect of the shrimp chips business in Kuala Jambi District, so financial feasibility research needs to be carried out to obtain the financial condition of the shrimp chips processing business, especially in the Poklahsar Tanjung Jaya Bersama. The purpose of the study is to analyze the financial feasibility of processed shrimp chips in the Poklahsar Tanjug Jaya Bersama Kuala Jambi Tanjung Jabung Timur. The research method used is a case study with a quantitative descriptive approach. Data was obtained through interviews, observations, and documentation studies, then analyzed using financial investment criteria, namely NVP (Net Present Value), BCR (Benefit Cost Ratio) and IRR (Internal Rate of Return). The results of the analysis showed that the shrimp chips processing business in Poklahsar Tanjung Jaya Bersama had a positive NPV value, BCR greater than 1, and IRR higher than the discount rate, which means that financially the business was declared viable to run and had the potential to increase group income and encourage the development of sustainable fisheries agribusiness in the coastal area of Kuala Jambi.